(untitled) (Nordic Journal of African Studies, 2005)
The headword of a dictionary entry serves different functions. First, it is a form which the user will first look up in the dictionary before reading other phonological, morphological, syntactic, semantic, and etymological information associated with it. Second, it is a form, which the user looks up to check for the spelling of the word. Third, for most entries, it serves as a representative or more technically a stem-from which a set of inflected forms of the same word could be generated by way of affixation. Fourth, it is a form that represents one meaning or several related senses. In order to achieve these functions, the ‘headword’ should be entered into the dictionary in its conventional spelling, i.e. its visual representation as in ordinary writing system and not its actual sequence of acoustic sounds as in pronunciation. In lexicography, the word in its conventional spelling (the orthographic word) is also referred to as a ‘citation-form’. However, there are a number of problems relating to citation-forms that are encountered by Bantu lexicographers in the course of compiling dictionaries of natural languages. These problems are such as the problems of alphabetizing headwords, especially verbs, adjectives, and words with pre-prefixes, the problem of entering unnatural forms, the problem of entering obsolete/unactivated stem-forms, and the problem of entering unidentifiable stems. This article discusses such problems faced by Bantu lexicographers and suggests ways of solving them.